Peningkatan Keterampilan Membaca Pemahaman Peserta Didik Menggunakan Model KWL (Know, Want to Know, Learned) pada Siswa Kelas IV SDN 07 Padang Gelanggang Kabupaten Agam - Azanni, Dinda; Azima, Nana Fauzana; Yenti, Yesni; Suriani, Ari (TSAQOFAH, 2025)
The low level of students’ understanding of reading texts, particularly in drawing conclusions and retelling content in their own words, forms the background of this study. The purpose of the research is to describe the improvement of students’ reading comprehension skills through the implementation of the Know, Want to Know, Learned (KWL) learning model. This study employed a Classroom Action Research (Penelitian Tindakan Kelas) method consisting of four stages: planning, implementation, observation, and reflection, involving 15 fourth-grade students at SDN 07 Padang Gelanggang. A combination of qualitative and quantitative approaches was used. Data were obtained through observations and assessments of reading comprehension skills in each cycle. The results show a significant improvement, with the instructional module assessment increasing from 85% in Cycle I to 96% in Cycle II. Teacher implementation rose from 75% to 96%, while student engagement improved from 82% to 92%. The average reading comprehension score also increased from 67.70 to 83.25. These findings demonstrate that the KWL model is effective in enhancing elementary students’ reading comprehension skills by promoting active engagement and gradual understanding of reading content.